RELIGIOUS MODERATION IN PUBLIC SCHOOLS; A SEARCH FOR A MODEL OF THE TEACHER'S ROLE - Anshari, Muhammad Redha; Surawan, Surawan; Fatimah, Cindy (Proceeding International Seminar of Islamic Studies, 2023)
This research aims to describe Islamic education teachers' role in building religious moderation values in elementary school Kabupaten Katingan and to know give values of religion moderation and supporting factors and inhibiting factors for building religious moderation at SDN Jahanjang dan SDN Asem Kumbang Kabupaten Katingan. This research was compiled by researchers using a qualitative approach with the type of field research and descriptive qualitative research methods. Collecting data using interview and documentation techniques. Data analysis was carried out by collecting data, reducing data, presenting and drawing conclusions. The validity of the data was carried out using triangulation of sources and techniques. The results of this study indicate that: 1. The role of Islamic education teachers in building religious moderation includes: a. The conservator as a PAI teacher is responsible for his attitude, b. Innovators, PAI teachers collaborate with all teachers from various religions, c. Transmitter, PAI teachers act as motivators and guides, d. Teacher organizer carries out innovative activities, e. Transformers, Islamic Education teachers translate values into figures for students; 2. The values of religious moderation that are built include fairness, balanced, simplicity, unity and brotherhood. 3. Supporting factors and inhibiting factors include: Supporting factors, namely the PAI teacher, who is an alumnus of an Islamic boarding school who has good experience and capacity. A community environment that supports school activities, especially religious activities. As for the inhibiting factor, namely the age of the student is very influential for the implementation of the religious development program, because new students are still adapting to go to school. Limited school facilities, as a forum for religious development, such as not having a prayer room, have made teachers have to be more creative in providing religious guidance in schools.